De-escalated radiation for human papillomavirus virus-related oropharyngeal cancer: evolving paradigms and future strategies - Chen, Allen M. (Frontiers in Oncology, 2023)
Human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma, which comprises an increasing proportion of all head and neck cancers, represents a unique entity with distinct clinical and molecular characteristics. Data has accumulated demonstrating that patients with HPV-positive oropharyngeal cancer have a significantly improved prognosis as a result of their exquisite radiosensitivity compared to their HPV-negative counterparts and thus can be targeted with de-escalated approaches using reduced doses of radiation. The overriding goal of de-escalation is to maintain the high cure and survival rates associated with traditional approaches while reducing the incidence of both short- and long-term toxicity. Although the exact reason for the improved radiosensitivity of HPV-positive oropharyngeal carcinoma is unclear, prospective studies have now been published demonstrating that de-escalated radiation can successfully maintain the high rates of cure and preserve quality of life for appropriately selected patients with this disease. However, these studies have been complicated by such factors as the relatively limited sample sizes, as well as the variability in treatment, inclusion criteria, and follow-up. How treatment paradigms will evolve, particularly in the era of precision medicine, is a provocative question and is the subject of this review.